Do mycorrhizal fungi drive speciation in Teagueia (Orchidaceae) in the upper Pastaza watershed of Ecuador? - Herrera Vargas, P. (2016)
The orchid genus Teagueia Luer (Orchidaceae, subtribe Pleurothallidinae) presents an extraordinary example of recent local evolutionary radiation. In principle, mutualisms might affect the origin of plant species via an effect on speci- ation. As orchids depend on mycorrhizal fungi for seed ger- mination and early plantlet development we tested whether certain mycorrhizal fungi are acting as drivers of this radiation in Teagueia species. Sampling was carried out near Baños in east Andean Ecuador. Roots were collected from a total of 11 flowering individuals of eight morphospecies (referred to as Teagueia spp). The whole ITS1-5.8S- ITS2 nrDNA region and part of the 28S nrDNA were amplified, cloned and se- quenced. Molecular phylogeny of the obtained sequences re- vealed four phylogenetic species of Tulasnellaceae and one of Atractiellales (Pucciniomycotina, Basidiomycota) associated with Teagueia spp. Tulasnelloid fungi were detected in all samples. Up to three different phylogenetic species of mycobionts were found associated with one Teagueia species. We found that co-occurring Teagueia species share mycobionts. All detected mycobionts had wide geographical distribution. Based on the available evidence we conclude that the extraordinary local radiation of Teagueia is most likely driven by other factors than by mycorrhizal fungi, but that mycorrhiza may be a key factor for the coexistence of so many closely related orchid species.